2018
DOI: 10.1097/aog.0000000000002795
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Screening for Syphilis in the Third Trimester of Pregnancy

Abstract: Using our baseline assumptions, our data support that in pregnancy, repeat screening for syphilis is superior to single screening during the first trimester and is both cost-effective and results in improvement in maternal and neonatal outcomes. When screening policies are being created for pregnant women, the cost-effectiveness of repeat screening for syphilis should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 16 publications
0
63
0
Order By: Relevance
“…Whether and how to rescreen women at increased risk for syphilis both early in the third-trimester and again at delivery are important questions. Although cost effectiveness analyses have not favored universal third-trimester rescreening of all pregnant women, this calculation may require adjustment especially for communities with a high-prevalence of syphilis [ 18 , 19 ]. While the mothers of the infants described in these case reports both screened negative for syphilis initially, neither was rescreened at delivery despite residing in communities with a high-prevalence of syphilis and having histories of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…Whether and how to rescreen women at increased risk for syphilis both early in the third-trimester and again at delivery are important questions. Although cost effectiveness analyses have not favored universal third-trimester rescreening of all pregnant women, this calculation may require adjustment especially for communities with a high-prevalence of syphilis [ 18 , 19 ]. While the mothers of the infants described in these case reports both screened negative for syphilis initially, neither was rescreened at delivery despite residing in communities with a high-prevalence of syphilis and having histories of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat screening can identify new infections in communities with high or rising syphilis prevalence, and has been shown to be a cost-effective public health prevention approach in some settings with higher syphilis prevalence or increasing prevalence in the community. 23,24 Although injectable penicillin is currently the only drug known to be effective in treating a syphilis-exposed fetus, alternatives to BPG during pregnancy are still commonly used in some countries, especially in the western Pacific (85% of countries), Africa (91%) and South East Asia (100%). Prior WHO guidance documents did not specifically caution against use of alternative treatment strategies, however, the 2016 and 2017 guidelines note that such strategies have not been proven effective in treating an exposed fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Universal third trimester screening has been proposed to address the rising incidence, but cost-effective analyses are mixed. [29][30][31] Albright et al 30 calculated that a national rate of 17 cases of primary and secondary syphilis per 100 000 women or higher would make it cost-effective. The national prevalence in 2013 was 0.9 cases per 100 000 women, which did not meet this threshold.…”
Section: Figurementioning
confidence: 99%
“…This has risen to 2.3 cases per 100 000 women in 2017 nationally, with a rate of 4.6 cases per 100 000 in California. 2 Conversely, Hersh et al 29 in 2018 demonstrated strong evidence that universal third trimester screening would be cost-effective and improve maternal and neonatal outcomes. Further supporting this approach, in a 2019 CDC study, researchers found that approximately half of all pregnant women with syphilis and one-third of pregnant women with early syphilis did not report any highrisk behaviors.…”
Section: Figurementioning
confidence: 99%